2012
DOI: 10.1038/aps.2012.67
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-pharmacodynamic modeling of diclofenac in normal and Freund's complete adjuvant-induced arthritic rats

Abstract: Aim: To characterize pharmacokinetic-pharmacodynamic modeling of diclofenac in Freund's complete adjuvant (FCA)-induced arthritic rats using prostaglandin E 2 (PGE 2 ) as a biomarker. Methods: The pharmacokinetics of diclofenac was investigated using 20-day-old arthritic rats. PGE 2 level in the rats was measured using an enzyme immunoassay. A pharmacokinetic-pharmacodynamic (PK-PD) model was developed to illustrate the relationship between the plasma concentration of diclofenac and the inhibition of PGE 2 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Zhang, Li, Guo, Liu, and Liu () reported that the IC 50 of DCF for inhibition of PGE 2 production in vivo was 0.5 ± 0.2 μg mL −1 . The mean plasma concentration of DCF was 512.92 ± 110.95 ng mL −1 24 h after i.m.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang, Li, Guo, Liu, and Liu () reported that the IC 50 of DCF for inhibition of PGE 2 production in vivo was 0.5 ± 0.2 μg mL −1 . The mean plasma concentration of DCF was 512.92 ± 110.95 ng mL −1 24 h after i.m.…”
Section: Resultsmentioning
confidence: 99%
“…The results with exception of Rahal et al (2008) showed that DCF was rapidly and well absorbed in cows, sheep and pigs. Zhang, Li, Guo, Liu, and Liu (2012) reported that the IC 50 of DCF for inhibition of PGE 2 production in vivo was 0.5 ± 0.2 μg mL −1 . The mean plasma concentration of DCF was 512.92 ± 110.95 ng mL −1 24 h after i.m.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…Concentrations of diclofenac in rat plasma and the incubation system were determined by HPLC with an ultraviolet detector, as previously described [32] with minor modifications. Briefly, for plasma samples, 50 μL plasma was spiked with 10 µL of 2 μg/mL chloroxazone as an internal standard and 100 µL acetonitrile.…”
Section: Drug Analysismentioning
confidence: 99%
“…30 min prior to operant experiments. The 5.6 mg/kg dose was chosen based on pilot data in our laboratory, and literature on diclofenac efficacy and potency against a range of nociceptive conditions [Euchenhofer et al, 1998;Yoshimi et al, 2010;Moller et al, 2012;Zhang et al, 2012].…”
Section: Drugmentioning
confidence: 99%